2021
DOI: 10.48175/ijarsct-1503
|View full text |Cite
|
Sign up to set email alerts
|

Cost Optimization of Cantilever Retaining Wall Using Flower Pollination Algorithm

Abstract: The flower pollination algorithm is nature-inspired in which it mimics the pollination process of the flowers. In this study, the cost of the cantilever retaining wall is optimized, which includes the cost of concrete and the cost of reinforcement steel. The eight design variables define the geometry of the RC wall. The external stability and structural stability are considered as constraints. Overturning, sliding, eccentricity, and bearing are considered external constraints. The structural stability constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Eccentricity As discussed earlier, due to large overturning moments, uplift can be generated at heel. To mitigate this, pressure at heel must not be negative and an additional check for eccentricity (e can be applied as done by various studies [17,20,21,39,41,43,47,49,54,63,68,71,80,83,88,93,101]. Generally it is defined as in equation ( 14); it should not be greater than one-sixth of the total base width (B.…”
Section: Geometric Requirements and Deflection Checkmentioning
confidence: 99%
See 2 more Smart Citations
“…Eccentricity As discussed earlier, due to large overturning moments, uplift can be generated at heel. To mitigate this, pressure at heel must not be negative and an additional check for eccentricity (e can be applied as done by various studies [17,20,21,39,41,43,47,49,54,63,68,71,80,83,88,93,101]. Generally it is defined as in equation ( 14); it should not be greater than one-sixth of the total base width (B.…”
Section: Geometric Requirements and Deflection Checkmentioning
confidence: 99%
“…Apart from that, comparisons with GA and PSO were drawn which showed that FPA outperforms GA and PSO in terms of variability. Kayabekir et al [75], Mevada et al [88], and Temür [99] also utilized FPA and evidence its capabilities and effectiveness. Yücel et al [97] produced a hybridized algorithm by combining the metaheuristic technique of FPA with a machine learning technique called artificial neural network (ANN).…”
Section: Flower Pollination Algorithm (Fpa) Mergos Andmentioning
confidence: 99%
See 1 more Smart Citation